2013
DOI: 10.1097/gme.0b013e318271e59b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bazedoxifene alone and with conjugated equine estrogens on coronary and peripheral artery atherosclerosis in postmenopausal monkeys

Abstract: Objective The objective was to evaluate the effects of bazedoxifene acetate (BZA), a new selective estrogen receptor modulator, on coronary and peripheral artery atherosclerosis and to determine if it would antagonize the atheroprotective effects of conjugated equine estrogens (CEE) in a monkey model. Methods Ninety-eight surgically postmenopausal monkeys (Macaca fascicularis) were fed a moderately atherogenic diet and then randomized to receive no treatment, or women’s equivalent doses of BZA (20 mg/day), C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
2
11
1
1
Order By: Relevance
“…We have reported separately that BZA was an estrogen antagonist capable of abrogating the effects of CEE on the monkey breast 18 , and endometrium 19 . We have also reported that BZA had no adverse effects on coronary and iliac artery atherosclerosis when given alone, but did attenuate the atheroprotective effects of CEE when given in combination 20 . In this communication we report on the effect of these interventions on the extent and severity of cerebral artery atherosclerosis.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…We have reported separately that BZA was an estrogen antagonist capable of abrogating the effects of CEE on the monkey breast 18 , and endometrium 19 . We have also reported that BZA had no adverse effects on coronary and iliac artery atherosclerosis when given alone, but did attenuate the atheroprotective effects of CEE when given in combination 20 . In this communication we report on the effect of these interventions on the extent and severity of cerebral artery atherosclerosis.…”
Section: Introductionmentioning
confidence: 56%
“…The mean plasma lipid and lipoprotein concentrations for the control and treatment groups over the experimental period were reported previously 20 and are presented in Table 1. There were no significant differences among the groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bazedoxifene-CE combination therapy in postmenopausal women and rodents results in a significant increase in bone mineral density [111,112] and a decrease in the frequency of hot flashes [113,114] while protecting the endometrium. In a postmenopausal monkey model, this TSEC treatment did not affect the adiposity and plasma lipid profile, but bazedoxifene was found to attenuate the atheroprotective effects of CE [115]. A molecular study of bazedoxifene function on energy and glucose homeostasis in OVX mice demonstrated that injection of recombinant RBP4 in normal mice results in insulin resistance [96].…”
Section: Estrogens Adipocytokines and Metabolic Syndromesmentioning
confidence: 99%
“…However, in a preclinical trial, treatment with bazedoxifene acetate (BZA), a new third-generation SERM, and conjugated equine estrogen (CEE) in combination did not show significant effects on plasma lipid profiles, and BZA treatment had no adverse effects on atherosclerosis but attenuated the atheroprotective effects of CEE in both the coronary and iliac arteries [6]. Raloxifene hydrochloride (RLX), a benzothiophene SERM, confers estrogen-like effects on lipids but anti-estrogenic effects on breast tissue and uterine endometrium.…”
mentioning
confidence: 99%